Workplace Recommendation with Temporal Network Objectives - Tomlinson, Kiran; Neville, Jennifer; Yang, Longqi; Wan, Mengting; Lu, Cao (2023 Knowledge Discovery and Data Mining, 2023)
Workplace communication software such as Microsoft Teams, Slack, and Google Workspace have become integral to workplace collaboration, especially due to the rise of remote work. By making it easier to access relevant or useful information, recommender systems for these platforms have the potential to improve efficient cross-team information flow through a company's communication network. While there has been some recent work on recommendation approaches that optimize network objectives, these have focused on static graphs. In this work, we focus on optimizing information flow, which is highly temporal and presents a number of novel algorithmic challenges. To overcome these, we develop tractable measures of temporal information flow and design efficient online recommendation algorithms that jointly optimize for relevance and cross-team information flow. We demonstrate the potential for impact of these approaches on a rich multi-modal dataset capturing one month of communication between 180k Microsoft employees through email, chats and posts on Microsoft Teams, and file sharing on SharePoint. We design an offline model-based evaluation pipeline to estimate the effects of recommendations on the temporal communication network. We show that our recommendation algorithms can significantly improve cross-team information flow with only a small decrease in traditional relevance metrics.